Image Captioning in Tamil Language using Encoder-Decoder Architecture - S, Thivaharan.; Srivatsun.G; S, Pranav Kiran.; J, Johan Benoni Raul. (Journal of Ubiquitous Computing and Communication Technologies, 2023)
Image captioning is the process of using clear, meaningful words to describe the characteristics of an image. This feature has wide applications in social networking applications such as Facebook and Instagram, and video streaming platforms such as YouTube and Netflix, where the need to verbalize an image or video is evident. Image captioning is also one of the most requested features in next-generation AI systems. It has huge applications in the Deep Learning domain. Much research is actively being done on image captioning, which can solve a good deal of real time problems such as the need for a system that can aid visually disabled people, creating effective captions that can be incorporated in self-driving vehicles, etc. This elaborate yet useful feature can be incorporated with the help of various technical concepts such as Natural Language Processing, Computer vision, Image Processing, etc. The image captioning feature has already been attempted on English language and with the help of extensive research and technical advancements these attempts have been fruitful and successful. Nowadays, there are many applications and models available based on image captioning of English language. This has paved a path for further advancements in this domain. A lot of research are now being undertaken to incorporate this highly useful feature with non-English languages. English being the native language for a relatively smaller proportion of people, it would be helpful for people whose native language is not English, to get their images captioned in the language of their choice. This research focuses on image captioning in Tamil language and its underlying methodology and architecture. Moreover, the paper also includes experiments related to this with the help of an image captioning model which uses a combination of Convolution Neural Network and Long Short -Term Memory models.
Keywords: Image Captioning in Tamil; Convolution Neural Network (CNN); Long Short -Term Memory (LSTM); Natural Language Processing (NLP); Computer Vision; Image Processing; Artificial Intelligence; Deep Learning